The Influence of Digital Ads, Influencer, and Customer Relations Management on Donation Decisions (Study at Masjid Nusantara Foundation) - Pras Purworo; Abdussalam Abdussalam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rapid development of digital technology has brought substantial changes to marketing strategies, including within the philanthropic sector. Social organizations, such as the Nusantara Mosque, are increasingly adopting various digital marketing tools to enhance donor participation. Among these, Digital Advertising (Digital Ads), Influencer Marketing, and Customer Relationship Management (CRM) are three widely utilized approaches to attract and retain donors. Nevertheless, the effectiveness of each strategy in influencing donation decisions remains insufficiently explored. This study seeks to analyze the extent to which Digital Ads, Influencers, and CRM affect donor decisions to contribute to the Nusantara Mosque. Employing a descriptive quantitative research design, data were collected through questionnaires distributed to 135 active donors of the Nusantara Mosque. The data were then analyzed using multiple regression with the assistance of SPSS 26. The findings indicate that both Digital Ads and CRM exert a positive and significant influence on donation decisions, whereas Influencers do not have a significant effect. Digital Ads contribute to raising awareness and facilitating access to donations, while CRM strengthens the relationship between donors and institutions, ultimately fostering donor loyalty. These insights highlight the importance for philanthropic organizations to design more effective digital marketing strategies. By optimizing Digital Ads and CRM, organizations can enhance donor engagement and fundraising performance. Conversely, influencer marketing strategies may need to be refined or integrated with other approaches to achieve a more substantial impact on donor decision-making.